Design and Implementation of System and Monitoring of the variables: Ph, oxygen level and temperature for piscicola cultivation pond in the International Nautical, Fluvial and Port Center - Johon Gutierrez-Jaraba; Fabio Pérez-Márquez (Sostenibilidad, Tecnología y Humanismo, 2018)
The water wealth in Colombia, the quality of its waters and the climate allow the artificial cultivation of fish or fish farming to be in frank development. This activity, whether handmade or industrial, must fulfill important aspects in relation to techniques and procedures. Water, an essential element for fish farming must be of quality and to achieve such property it is necessary to measure the variables “ph”, “dissolved oxygen” and “temperature”. The purpose of this work was to study the traditional procedure and then design a measurement monitoring system for these variables with the use of sensors, conditioning circuits, analog-digital conversion, generation of historical records and a user interface. The study was conducted in a pond for fish farming, gathering detailed information and selecting equipment and elements appropriate for the implementation of a new system. The design was done, device tests were performed and a user manual was developed. The result was a system capable of determining, visualizing and storing the results of the determining parameters in water quality. At the conclusion of the study, a pH / OD / temperature meter is obtained, with the ability to determine, visualize and store data. As a recommendation, the design of a meter calibration calendar is suggested.